(untitled) (Global Journal of Science Frontier Research, 2021)
House fly "Musca domestica" Linnaeus is a common insect widely distributed all over the world and is one of the domestic insect pests found associated with human and animal. Due to their habits and habitats, house flies are able to transmit several pathogenic microorganisms to man such as: bacteria, fungi and virus. House flies are not just annoying human and animal, but they also have been known as vectors of infectious microorganisms either mechanically or biologically. Chemical insecticides have been used for many years and have been known as the most effective approach in house fly management but due to their side effects on the environment and the increasing development of pest resistance to each new chemical, studies tended to explore new alternative methods in pest control. Biological methods including different predators, parasites, entomopathogenic micro-organisms and botanical extracts showed in the last years a practical and effective ecofriendly method to control insect pests including house fly and at the same time safe on human and animal.